1977
DOI: 10.1007/bf00385986
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ribosomal and messenger RNA synthesis in excised Jerusalem artichoke tuber slices

Abstract: RNA synthesis was studied in Jerusalem artichoke (Helianthus tuberosus L.) tuber slices immediately following excision and during the early period of aging in water. Incorporation of [(3)H]adenosine into RNA was detected as early as 20 min after excision. Measurement of the specific activities of RNA (cpm/μg) and of ATP showed that RNA synthesis proceeded at a constant rate for the first several hours of aging and then increased moderately. [(3)H]adenosine was incorporated into polysomes throughout the aging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It is known from previous studies that in storage organs of plants such as potato and Jerusalem artichoke tubers, most of the ribosomes are present in the form of monosomes (Byrne and Setterfield 1977,1978, Ishizuka et al 1981, Kahl 1971, Sato et al 1980, Sparkuhl et al 1976. Wielgat and Kahl 1979.…”
Section: Results and Discussion Poiysomal Profilesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known from previous studies that in storage organs of plants such as potato and Jerusalem artichoke tubers, most of the ribosomes are present in the form of monosomes (Byrne and Setterfield 1977,1978, Ishizuka et al 1981, Kahl 1971, Sato et al 1980, Sparkuhl et al 1976. Wielgat and Kahl 1979.…”
Section: Results and Discussion Poiysomal Profilesmentioning
confidence: 99%
“…involves RNA and protein synthesis (Byrne and Setter-Changes in the profiles of ribosomes m these tissues field 1977 1978 Kahl 1971, Leaver andKey 1967, after wounding and hormone-treatment have been stud- Minocha andDiBona 1979, Sato et al 1980). Whereas ied by several workers (Byrne and Setterfield 1977, in tissues like potato, the wounding response involves 1978, Sato et al 1980, Wielgat andKahl 1979). Woiind-DNA synthesis and cell division (Watanabe and Imaseki ing causes a rapid aggregation of nbosomes to form 1973) in Jerusalem artichoke these events do not occur polysomes.…”
Section: Introduction Proportion Of Cells In the Explant Undergo Syncmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaver and Key (24) reported that the level of polyribosome formation in wounded carrot tissues depended on previous RNA synthesis. Rapid formation of polysomes was observed in slices of sugar beet (37) and during activation of artichoke tuber cells (5,32), and was correlated with protein synthesis (2,17,20).…”
mentioning
confidence: 99%
“…The time-dependent development of responsiveness of a given tissue toward GA3 evidently is a widespread phenomenon (12,35,38,40,41 first 2 h after wounding sugar beet root (37) and Jerusalem artichoke tuber tissue (5). Later on, radioactivity is progressively incorporated into rRNA, also (5,16,37). Whereas GA3 has no effect in freshly wounded tuber tissue, it strikingly affects the incorporation of uridine into polysomes of tissue after 18 h of wound healing (Fig.…”
mentioning
confidence: 99%